Influência da hidroelétrica de Tucuruí sobre aspectos da biologia populacional de peixes detritívoros do Rio Tocantins (PA-Brasil) - Travassos, Fábio Alexandre [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of this study is to investigate the influence of Hydroelectric Power Plant of Tucuruí (HPP Tucuruí), state of Pará, Brazil, on the species of fish Curimata acutirostris, Curimata inornata, Curimata vitatta, Psectrogaster amazonica and examining the weight-length relationships, allowing one to calculate the condition factor. The analyzes also the sex ratio were observed among individuals. The data comes from experimental fisheries conducted by the Program of Fisheries and Ichthyofauna ELETRONORTE/ELETROBRÁS, having been captured among the four studied species, 3,076 individuals in the downstream area of the reservoir, while the area upstream was captured 2,936 individuals. As results were observed that significant differences (p<0.05) were found between the upstream and downstream for the four species, as the standard length and total weight, with the highest values were always observed downstream. The condition factor for C. inornata, C. inornata and P. amazonica, significam diferentes (p<0.05) were found between the upstream and downstream, and the highest values were always observed downstream. To C. vitatta also was no difference, but the median value is more in upstream of the plant. For the region upstream of the plant, the species C. inornata, C. vitatta and P. amazonica showed the increase in weight-length relationships positive allometric, however, to C. acutirostris allometric growth was negative. In the downstream region, the species C. acutirostris, C. inornata and P. amazonica had showed negative allometric growth, with only a C. vitatta had another growth isometric. For the four species studied, the occurrence of females in snippets of influence was higher. The results presented clearly demonstrate that environmental conditions downstream are generally are more favorable survival of the species ...

O objetivo deste trabalho é verificar a influência da Usina Hidrelétrica de Tucuruí (UHE Tucuruí), Estado do Pará, Brasil, sobre as espécies de peixe Curimata acutirostris, Curimata inornata, Curimata vitatta e Psectrogaster amazonica, analisando a relação entre o peso corporal e o comprimento corporal padrão, permitindo calcular o fator de condição. Nas análises também foram verificadas as proporções sexuais entre os indivíduos. Os dados provêm de pescarias experimentais realizadas pelo Programa de Pesca e Ictiofauna da ELETRONORTE/ELETROBRÁS, tendo sido capturados entre as quatro espécies estudas, 3.076 indivíduos na área jusante do reservatório, enquanto que na área montante capturou-se 2.936 indivíduos. Como resultados ficaram constatados que foram encontradas diferenças significativas (p<0,05) entre montante e jusante, para as quatro espécies, quanto ao comprimento padrão e peso total, sendo que os maiores valores foram sempre observados a jusante. O fator de condição, para a C. inornata, C. inornata e P. amazonica, foram encontradas diferenças significativas (p<0,05) entre montante e jusante, sendo que os maiores valores foram sempre observados a jusante. Para a C. vitatta, também houve diferença, mas a mediana do valor foi maio a montante da usina. Para a região de montante da usina, as espécies C. inornata, C. vitatta e P. amazonica apresentaram os crescimento na relação peso/comprimento tipo alométrico positivo, no entanto, para a C. acutirostris o crescimento foi alométrico negativo. Na região de jusante, as espécies C. acutirostris, C. inornata e P. amazonica tiveram a relação de crescimento tipo alométrico negativo, sendo que apenas a C. vitatta teve outro crescimento, isométrico. Para as quatro espécies estudas, a ocorrência de fêmeas nos trechos de influência do barramento foi maior. Os resultados apresentados demonstram claramente que ...
Keywords: Peixe; Peixe - Pesos e medidas; Usinas hidrelétricas; Corpo - Peso; Corpo - Tamanho; Fishes